Pain management and coping strategies for primary dysmenorrhea: A qualitative study among female nursing students - Elia Fernández‐Martínez; Jorge Pérez‐Corrales; Domingo Palacios‐Ceña; Ana Abreu‐Sánchez; María Teresa Iglesias‐López; Pilar Carrasco‐Garrido; Juan Francisco Velarde‐García (Wiley, 2022)
Abstract Aim Primary dysmenorrhea is a problem that affects both young and adult women, with a significant impact on their daily lives. This pain is primarily managed through the consumption of non‐steroidal anti‐inflammatories and non‐pharmacological approaches such as exercise, acupressure and heat. The present study aimed to describe how Spanish university students manage dysmenorrhea. Design Qualitative case study. Methods Nursing students (N = 33) from the region of Andalusia (Spain) participated in focus groups. A purposive sampling method was used, and the data were collected through videoconferencing and subsequently analysed thematically. The guidelines for conducting qualitative studies established by the consolidated criteria for reporting qualitative research (COREQ) and the standards for reporting qualitative research (SRQR) were followed. Results Four principal themes were identified: (a) Strategies for pain management; (b) using painkillers; (c) choosing the ideal treatment; (d) non‐pharmacological interventions. Conclusions The nursing students experienced difficulties in managing primary dysmenorrhea, they self‐medicated, expressed reluctance to seek professional medical advice, used non‐pharmacological strategies and seeked advice from other women within their family/social circle.